Tentative list of endemic vascular plants of the Zeravshan Mts in Tajikistan: distribution, habitat preferences and conservation status of species - Nowak, Arkadiusz; Nobis, Marcin (Biodiversity: Research and Conservation, 2011)
Based on literature data and own fieldwork in the Zeravshan Mts in Tajikistan (Middle Asia), the taxonomic structure, distribution, habitat preferences as well as conservation status of a group of 86 species of vascular plants of endemic character are presented. The tentative list of exclusive endemic plants for the Zeravshan Mts was compiled. They belong to 25 families. The richest is the genus Astragalus with 11 species followed by Cousinia (8), Allium (5) and Scutellaria (3). The study has shown that the eastern subregions of the range are richest in endemics, especially, the Mogien-Daria, Seven Lakes, Pastrud-Daria, Ksztut and Yagnob valleys and Kuli-Kalon Plateau. The endemics studied are stenochoric species with very small number of known locations, mainly between one and two. The mean value of the range of the studied endemics is ca. 1140 km2. The most numerous endemic groups have been recorded at altitudes of around 1,800-2,100 and 2,700-3000 m a. s. l. The habitats harboring the richest group of endemics are rock screes, alpine forests, steppes and semi-savannas, alpine meadows, solid rocks, xerothermophilous shrubs and pastures. Almost half of the endemics have narrow ecological amplitude occurring in only one habitat type. The most important threats to Tajik endemics are intensive grazing and erosion of soils, as well as denudation. Most vulnerable types of vegetation to the human impact are forest and scrub communities. For effective protection of endemics in the Zeravshan Mts, a national park and a net of nature reserves has to be funded.